간호사의 보수교육 프로그램 평가에 대한 중요도 인식 - 조미영(Jho, Mi Young) (Sŏngin Kanho Hakhoe chi, 2013)
Purpose: The purpose of this study was to explore the nurses' perception of the importance of evaluating continuing nursing education programs. Methods: Subjects were 465 nurses enrolled in continuing nursing education programs at five university hospitals in Seoul and Gyeonggi-do. Data were collected from September 20, 2011 to October 13, 2011. The instrument was developed by the author through a literature review. Content validity was established from a panel of six experts. Data were analyzed using SPSS/WIN 18.0 program. Results: The purpose of the program was rated as the most important domain by the subjects. Interestingly, 'program outcome' and 'effectiveness of program' were ranked below the mean (M=$3.64{±}0.75$). These two domains were influenced by the district of work and the type of institution. The position of the participants at their institutions made the significant differences on their perception of 'program purpose.' Conclusion: The results of this study might aid us to have better understanding for what nurses perceive the importance of evaluating continuing nursing education programs. This information might be able to be used for improving programs. Further studies are needed to explore the validity of the instruments to evaluate continuing nursing education programs.